PEMBUATAN MODEL NAVIGASI BERBASIS AUGMENTED REALITY DENGAN METODE MARKERLESS DI GEDUNG RISE CENTER - Santi, Amelia Nur; Hidayat, Safaruddin; Sahid Agustian (Universitas Majalengka, 2023)
The current navigation system is crucial as it can facilitate human location search. However, only a small number of buildings in Indonesia implement indoor navigation systems. An indoor or building-based Augmented Reality navigation system can save time because it combines virtual objects with the real physical world through a 3D path alignment that corresponds to real-world features. This system will assist users in finding their way within the RISE Center building when they first arrive or when they have difficulty locating specific rooms. The system uses markerless Augmented Reality and can determine the user's initial location when they are at the starting point or when they scan QR codes at specific points. This system has been tested in the RISE Center building of the Faculty of Engineering and Science at Ibn Klahdun University (UIKA), Bogor. The results demonstrate that the system can serve as an effective platform for displaying location information without requiring an internet connection.